2020
DOI: 10.1097/brs.0000000000003237
|View full text |Cite
|
Sign up to set email alerts
|

Should Sagittal Spinal Alignment Targets for Adult Spinal Deformity Correction Depend on Pelvic Incidence and Age?

Abstract: Study Design. Retrospective analysis. Objective. Determine whether deformity corrections should vary by pelvic incidence (PI). Summary of Background Data. Alignment targets for deformity correction have been reported for various radiographic parameters. The T1 pelvic-angle (TPA) has gained in applications for adult spinal deformity (ASD) surgical-planning since it directly measures spinal alignment separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Patients with a small PI have less sagittal compensation ability, and the requirements for reconstruction of lumbar lordosis are stricter. 24 In our study, mechanical complications were signi cantly correlated with GAP scores. The average GAP scores were 6.9±2.0 and 10.9±2.4 in groups A and B, respectively.…”
Section: Radiographic Outcomes By Groupsupporting
confidence: 53%
“…Patients with a small PI have less sagittal compensation ability, and the requirements for reconstruction of lumbar lordosis are stricter. 24 In our study, mechanical complications were signi cantly correlated with GAP scores. The average GAP scores were 6.9±2.0 and 10.9±2.4 in groups A and B, respectively.…”
Section: Radiographic Outcomes By Groupsupporting
confidence: 53%
“…The association between increasing PI and larger TPA in AS patients with thoracolumbar kyphosis might be significant for the surgical design. Protopsaltis et al [28] also found that TPA was significantly correlated with PI in adult spinal deformity and suggested that the targets for sagittal spinal alignment increase with increasing PI.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the influence of PI on compensation and notably the interplay of PI, PT and SS to achieve pelvic retroversion was also observed in this study. Previous work has shown that the ability to retrovert the pelvis, by increasing PT, is limited by PI, in addition to a minimal value of SS of 0°, a horizontal sacral endplate 10 , 22 . A smaller PI means the pelvis has a more vertical shape, a lower SS and as a result, it is generally observed that these individuals have less capacity to retrovert their pelvis.…”
Section: Discussionmentioning
confidence: 99%